Novel monolithic catalysts for VOCs removal: A review on preparation, carrier and energy supply. (December 2022) - Fu, Kaixuan; Su, Yun; Zheng, Yanfei; Han, Rui; Liu, Qingling
Abstract: Volatile organic compounds (VOCs) are considered the culprit of secondary air pollution such as ozone, secondary organic aerosols, and photochemical smog. Among various technologies, catalytic oxidation is considered a promising method for the post-treatment of VOCs. Researchers are sparing no effort to develop novel catalysts to meet the requirements of the catalytic process. Compared with the powdered or granular catalysts, the monolithic catalysts have the advantages of low pressure drop, high utilization of active phases, and excellent mechanical properties. This review summarized the new design of monolithic catalysts (including new preparation methods, new supports, and new energy supply methods) for the post-treatment of VOCs. It addressed the advantages of the new designs in detail, and the scope of applicability for each new monolithic catalyst was also highlighted. Finally, the highly required future development trends of monolithic catalysts for VOCs catalytic oxidation are recommended. We expect this work can inspire and guide researchers from both academic and industrial communities, and help pave the way for breakthroughs in fundamental research and industrial applications in this field. Graphical abstract: The latest research progress of monolithic catalysts is divided into three parts: new preparation methods, new supports, and new energy supply methods. This manuscript addressed the advantages of these new designs in detail, and the scope of applicability for each new monolithic catalyst was also highlighted. Image 1 Highlights: The characteristics of the novel monolithic catalysts for VOCs are summarized. High activity, low cost, and rapid preheating are the targets for the novel monolithic catalysts. This review focuses on the beneficial effects of every new monolithic catalyst. The perspectives and future challenges for the monolithic catalysts are proposed.